2003
DOI: 10.1080/15428110308984859
|View full text |Cite
|
Sign up to set email alerts
|

An Occupational Exposure Assessment of a Perfluorooctanesulfonyl Fluoride Production Site: Biomonitoring

Abstract: This investigation randomly sampled a fluorochemical manufacturing employee population to determine the distribution of serum fluorochemical levels according to employees' jobs and work areas. Previous analyses of medical surveillance data have not shown significant associations between fluorochemical production employees' clinical chemistry and hematology tests and their serum PFOS and perfluorooctanoate (PFOA, C(7)F(15)COO(-)) concentrations, but may have been subject to nonparticipation bias. A random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 25 publications
(38 reference statements)
0
21
0
1
Order By: Relevance
“…Upper high range of PFOS concentrations detected in the serum of production plant workers (Olsen et al, 2003) and upper high range of plasma of bottlenose dolphins (Houde et al, 2005).…”
Section: Statistical Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Upper high range of PFOS concentrations detected in the serum of production plant workers (Olsen et al, 2003) and upper high range of plasma of bottlenose dolphins (Houde et al, 2005).…”
Section: Statistical Evaluationmentioning
confidence: 99%
“…Results were obtained in units of counts per minute (cpm) and were normalized on a plate-by-plate basis, using control wells. Within each plate, raw responses were averaged for each treatment and scaled Low concentration of triclosan observed in human plasma (Allmyr et al, 2006) 2 mg ml À1 Low concentration detected in Charleston Harbor water samples (Fair et al, 2009) 20 mg ml À1 High concentration detected in Charleston Harbor water samples (Fair et al, 2009); low concentration observed in human breast milk and high concentration in human plasma of exposed individuals (Allmyr et al, 2006) High concentration of PFOS detected in plasma of bottlenose dolphins in Charleston, SC (Houde et al, 2005) and high concentrations of PFOS detected in the serum of random blood donors (Olsen et al, 2003) 30 mg ml À1…”
Section: Statistical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…18−25 Previous studies noted that workers in fluorochemical production plants are a subgroup that have an exceptionally high body burden of PFAAs. 26,27 However, possible sources and routes of exposure to PFAA isomers in occupationally exposed workers are not well-characterized. Our previous study revealed that high levels of PFAAs were found in the ambient environment of a perfluorosulfonate (PFSA) manufacturing facility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Research shows that levels of PFOA in wildlife range from 0.05 ng/mL in the blood of cod collected from European waters to 8.14 ng/mL in the plasma of loggerhead sea turtles from North America [10,11]. It can be also accumulated in creatures through water, food and atmosphere, causing the decrease in fertility rate, birth weight and other immune system diseases [12,13,14,15,16,17,18]. Although the environmental protection agency of the United States (US-EPA) and the European environment agency (EEA) have adopted an industrial program in order to reduce the global emissions of PFOA [19,20], the remained PFOA in the environment still has potential risk on humans.…”
Section: Introductionmentioning
confidence: 99%